Applied and conceptual approaches to evidence-based practice in research and academic libraries - Thorpe, Clare; Howlett, Alisa (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
Evidence-based practice is an approach to professional practice that involves a structured process of collecting, interpreting and applying valid and reliable research and evidence to support decision-making and continuous service improvement in professional practice. This paper reports on emerging initiatives in evidence-based practice at the University of Southern Queensland (USQ) Library, a regional multi-campus university in Australia. It demonstrates how evidence-based practice forms part of our organisational strategy to engage with our community and society. The case study describes a new model of embedding evidence-based practice through a role explicitly dedicated to developing the library’s evidence base. While other libraries may have a person responsible for assessment, performance metrics or data analysis, the Coordinator (Evidence-Based Practice) has a broader mandate – to work with library staff to develop tools, skills and expertise in evidence-based practice. The paper will describe why this role was created and how the Coordinator is working to engage with library staff to understand their business and the evidence needed to support service improvement for the Library. By doing this, USQ Library is building the capacity to demonstrate value to stakeholders, gain a deeper understanding of clients’ needs and experiences, promote robust decision-making and improve service delivery. The paper also outlines an initiative led by the Coordinator (Evidence-Based Practice) to develop a conceptual model of evidence-based practice within academic libraries at the organisational, rather than individual level. Current models of evidence-based library and information practice apply predominantly to individuals. Informed by relevant literature and 16 semi-structured interviews with library professionals from Australian and New Zealand university libraries, three themes emerged to describe how evidence-based practice might be experienced at the organisational level. The lived experience at USQ Library and our research investigations suggest that being evidence-based provides benefits to an academic library’s culture, practice and impact.